Speak the language of tolerance - Abd Razak, Dzulkifli (2007)
The ushering in of the New Year this time was rather unique in that it coincided with one of Islam’s most sacred moments during Aidiladha or the Feast of Sacrifice, in conjunction with the annual pilgrimage or hajj. It is an extra special occasion as Malaysia is also celebrating its 50 years of nationhood this year, and Aidiladha espouses the "spirit of sacrifice" as did those who fought for our independence. In fact, historically, the sense of sacrifice that exudes from Aidiladha goes beyond any personal or national experiences. Rather, it is based on total devotion and selflessness, a value that is rare in today's world. Yet, some 50 years ago, this was the exact value that shaped Malaya, and subsequently Malaysia, with the cooperation of Sabah and Sarawak.